Erythrocyte Sedimentation Rates and Leukogram Changes in Canine Model of Osteoarthritis (Nigerian Journal of Physiological Sciences, 2021)
Summary: Inflammatory markers such as erythrocyte sedimentation rates (ESR) have been evaluated in humans with osteoarthritis (OA). However, there has been no record of evaluation of ESR during OA in dogs. Changes in erythrocyte sedimentation rates (ESR) and leukogram functions were evaluated following experimental knee osteoarthritis (OA).Ten dogs of both sexes with (mean weight = 12.4 ± 1.8kg) were used. Experimental OA was induced in the right knee, using the groove model and confirmed radiographically using evidence of joint space narrowing and presence of osteophytes. Gait was assessed subjectively and scores (GAS) were assigned. Blood was obtained fortnightly for the determination of ESR, total white blood cell (tWBC), neutrophil and lymphocyte counts, while knee radiographs were obtained fortnightly for twelve weeks. Radiographic scores (RAS), GAS, ESR and leukocyte parameters between the different time points were compared with ANOVA. Correlation between parameters was evaluated using Pearson’s correlation. A “P” value less than 0.05 was considered significant. Both ESR and neutrophil/lymphocyte (N/L) ratio increased from week 0 to week 12 of OA. However, tWBC, neutrophil and lymphocyte counts did not differ significantly. Both GAS and RAS increased up to week 4 and 6 of OA respectively. Erythrocyte sedimentation rates was significantly (p= 0.033) and positively correlated (r=0.793) with N/L ratio, but negatively and slightly correlated (r= -0.843) with GAS. There was no significant correlation between ESR and RAS. It was concluded that both ESR and N/L ratio might be useful in monitoring progression of OA in dogs..